ANALISIS STRATEGI PENGEMBANGAN KAMPUNG PERIKANAN BUDIDAYA RUMPUT LAUT DI DESA LONTAR KABUPATEN SERANG - Gumilar, Iwang; Heryadi, Haikal Dapa; Suryana, Asep Agus Handaka; Nurhayati, Atikah (JURNAL PERIKANAN TROPIS, 2024)
The amount of seaweed production in Lontar Village which decreases every year needs to be analyzed to increase the amount of seaweed production in Lontar Village. In this study, an analysis of internal and external factors of seaweed cultivation business in Lontar Village will be conducted. Formulation of development directions using SWOT analysis. Based on the results of IFAS and EFAS analysis, internal and external factors have 5 factors. Strengths include people's interest in large seaweed farming businesses, labor is easy to obtain from families and communities, seaweed cultivation technology is simple and easy, large seaweed cultivation areas are available and harvesting and maintenance periods can be arranged. Weaknesses include lack of knowledge and skills in the cultivation business, seaweed is susceptible to pest and disease attacks, the quality and quantity of seeds are not supportive, there is no seaweed processing industry and poor water quality that affects harvesting. Opportunities include export market potential, superior products of government programs, seaweed processing industry, seaweed processing technology and facilities and infrastructure. Threats include the threat of climate change, lack of training from extension workers, fluctuating seaweed prices, loss of generations of seaweed farmers and assistance from the government has not met the needs of farmers and has not been evenly distributed. Based on the results of the matrix analysis, the right strategy applied to seaweed farming business in Lontar Village is the S-O (Progressive) strategy. The S-O (Progressive) strategy consists of investing in innovative technology and training, creating a sustainable seaweed processing industry, utilizing government program support, optimizing the use of cultivated areas and taking advantage of export opportunities. Keywords: SWOT analysis, Seaweed, Lontar Village.